The Ethics Committee as Gatekeeper, Enemy, Censor, or Partner? The Process of the Ethical Evaluation of Social Research with Sex Workers (Diametros, 2023)
The purpose of the paper is to present the challenges and difficulties that may be encountered in the process of the evaluation of qualitative research on sex workers by ethics committees. Such research is usually subject to review by ethics committees because of the risk of harm to participants, who are considered “vulnerable”. At the same time, due to the social stigma arising from the provision of sex services, researchers, research participants, and ethics committee members may have their own ideas and expectations about how ethical research in this area should be conducted. Referring to the experience of researchers from common law countries, this paper will discuss how these expectations and the requirements of ethics committees collide, confronting the researcher with the need to meet the divergent or even contradictory expectations of various social actors. I will also propose alternative procedures for Polish ethics committees to ensure that the process of obtaining their approval is more democratic and open to the diverse needs of both researchers and research participants.
Keywords: ethics committees; qualitative research; stigmatization; stigma; sex work